Pengaruh Penerapan Manajemen Sumber Daya Manusia pada Kinerja Organisasi dengan Mediasi Manajemen Talenta - Agustinus Setyawan (Program Sarjana Manajemen Universitas Internasional Batam, 2019)
This study aims to investigate the influence of human resource management practices to organization performance and talent management as a mediating factor in the relationship. This research uses methodology with an explanatory study by testing three hypotheses. A hundred managers from several coal companies in East Kalimantan Province are collected as a sample in this research. SEM (Structural Equation Model) is used to analyze the data which is collected by questionnaire. The result of this study found that: (1) Human resource management practices affect talent management positively and significantly; (2) Human resource management practices doesn’t affect organization performance significantly; (3) Talent management affects organization performance positively and significant. This research has a managerial implication to guide the decision maker in the company or manager in the human resource management to implement talent management to improve organization performance.